Complex engineering service systems concepts and research - Ng, Irene C. L. (Decision engineering, 2011)
For manufacturers of complex engineering equipment, the focus on service and achieving outcomes for customers is the key to growth. Yet, the capability to provide service for complex engineered products is less understood. Taking a trans-disciplinary approach, Complex Engineering Service Systems covers various aspects of service in complex engineering systems, with perspectives from engineering, management, design, operations research, strategy, marketing and operations management that are relevant to different disciplines, organisation functions, and geographic locations. The focus is on the many facets of complex engineering service systems around a core integrative framework of three value transformations ? that of material/equipment, information and people. Complex Engineering Service Systems is the outcome of the EPSRC/BAE Systems S4T (Service Support Solutions: Strategy and Transition) research programme of 10 universities and 27 researchers, which examined how high-value manufacturers of complex engineering products adapt to a multi-partnered environment to design and deliver value in a service system. Complex Engineering Service Systems aims to be the main source of knowledge for academics and professionals in the research and practice of contracting, managing, designing, leading, and delivering complex engineering service systems. The book takes a value-based approach to integrating equipment and human factors into a total service provision. In doing so, it aims to advance the field of service systems and engineering.